THE EFFECT OF COLONY TOPOGRAPHY ON CLIMATE SIGNALS IN CORAL SKELETON - Cohen A.L.; Hart S.R. (My University, 1997)
The stable oxygen isotope composition of the aragonitic skeleton of hermatypic corals is a potential archive of paleotemperature and rainfall data. Biological processes also influence coral δ18O although it has been difficult to determine which processes are involved and whether or not they dominate the stable isotope signal. We show here that colony topography, or surface bumpiness, is associated with significant differences in δ18O, δ13C, and the timing of high-density band formation between same-age corallites in the central and fastest-growing region of a coral colony. These differences reflect changes experienced by individual corallites as they grow from the summit of a bump toward the bottom of a valley. Corallites on the bump record isotopic temperatures more than 1°C higher and accrete high-density skeleton about 2 months earlier than their valley counterparts just 20 mm away. We propose that these changes are not caused by corallite ''aging'' but rather by changes in the overall rate and timing of light-enhanced calcification, which is lower and occurs later in shaded valleys than it does on exposed bumps. Although we conclude that sea temperature is the dominant influence on δ18O values in our coral, our results show that significant isotopic variations may be expected over a small surface area in a single colony. The production of accurate and reproducible coral-based climate records thus requires an understanding of the complexities of coral growth processes and incorporation of this knowledge into sampling strategies and interpretation of data.